Mechanical Model to Analyse Multilayer Geosynthetic Reinforced Granular Layer in Column Supported Embankments. (2016) - Ghosh, Balaka; Fatahi, Behzad; Khabbaz, Hadi
Abstract: The objective of this paper is to develop a mechanical model to predict the behaviour of a multilayer geosynthetic reinforced granular fill soft soil system improved with controlled modulus columns beneath the embankment. Deformation of geosynthetics embedded granular layer due to bending and shear is considered in this study. Therefore, geosynthetic reinforced granular fill has been idealised as a reinforced Timoshenko beam while the columns and the soft soil have been idealised as a layer of linear springs with varied stiffness. Plane strain conditions are considered for the loading and reinforced foundation soil system. Tension developed in the geosynthetics, rotation and settlements of the improved soft ground are predicted using the proposed model. This study shows the effects of multilayer geosynthetics on the settlement response of the granular layer. A notable reduction of the settlement has been observed as a result of the using multilayer weaker geosynthetic reinforcement system when compare to one stronger geosynthetics layer. It is also observed that the top reinforcement layer is subjected to maximum mobilised tension at the column edge whereas bottom reinforcement layer is more effective in controlling the deflection in the middle of two columns.